Practical guide to ICP-MS a tutorial for beginners - Thomas, Robert, 1949- (Boca Raton : Taylor & Francis, 2013)
"Presenting an in-depth discussion of the fundamental principles, analytical advantages, and practical capabilities of ICP-MS, this volume offers key concepts in a reader-friendly format suitable for those with limited knowledge of the technique. Written by an insider with more than 20 years experience in product development, customer support, and technical marketing for an ICP-MS instrument vendor, the book highlights this powerful ultra trace-element technique as a practical solution to real-world problems. The new edition has been updated and revised to cover new developments and updates to existing applications and reflects the significant new technology introduced by vendors since the second edition published"--
ch. 1. An overview of ICP-MS -- ch. 2. Principles of ion formation -- ch. 3. Sample introduction -- ch. 4. Plasma source -- ch. 5. Interface region -- ch. 6. Ion-focusing system -- ch. 7. Mass analyzers : quadrupole technology -- ch. 8. Mass analyzers : double-focusing magnetic sector technology -- ch. 9. Mass analyzers : time of flight technology -- ch. 10. Mass analyzers : collision/reaction cell and interface technology -- ch. 11. Ion detectors -- ch. 12. Peak measurement protocol -- ch. 13. Methods of quantitation -- ch. 14. Review of interferences -- ch. 15. Sample preparation -- ch. 16. Routine maintenance -- ch. 17. Alternative sample introduction techniques -- ch. 18. Coupling ICP-MS with chromatographic techniques for trace element speciation -- ch. 19. Common ICP-MS applications -- ch. 20. Emerging ICP-MS application areas -- ch. 21. Comparing ICP-MS with other atomic spectroscopic techniques -- ch. 22. How to select an ICP mass spectrometer : some important analytical considerations -- ch. 23. Final thoughts.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Inductively coupled plasma mass spectrometry; Electronic books